Kajian Perbandingan Kelayakan Usaha Dua Petani Stroberi Menggunakan Pendekatan Revenue-Cost Ratio - Samsul Arifin; Ulya Rahmah; Ervina Rizki Yani (AGRITEKH (Jurnal Agribisnis dan Teknologi Pangan), 2026)
Strawberry farming is a high-value horticultural activity with strong potential to generate economic benefits when managed efficiently. In practice, however, the level of financial feasibility often varies among farmers, even under similar agroecological conditions. This study aims to analyze production cost structure, revenue, income, and financial feasibility of strawberry farming using the Revenue–Cost Ratio (R/C) approach, as well as to compare the economic performance of two strawberry farmers in Sugihmukti Village, Pasir Jambu District, Bandung Regency. This research employed a quantitative descriptive method with a comparative case study approach. Data were collected through structured interviews and field observations over one production season. Production costs were classified into fixed and variable costs, followed by calculations of total cost, revenue, income, and R/C Ratio for each farming unit. The results indicate that both strawberry farms are financially feasible, with R/C Ratios greater than one. Farmer 1 achieved an R/C Ratio of 2.04 and a net income of IDR 293,928,000 per year, while Farmer 2 recorded an R/C Ratio of 1.16 with a net income of IDR 89,014,000 per year. Although Farmer 2 generated higher total revenue, higher production costs reduced overall profitability.